Edoxaban in atrial fibrillation patients with established coronary artery disease: Insights from ENGAGE AF–TIMI 48. Issue 2 (1st March 2019) - Zelniker, Thomas A; Ruff, Christian T; Wiviott, Stephen D; Blanc, Jean-Jacques; Cappato, Riccardo; Nordio, Francesco; Mercuri, Michele F; Lanz, Hans; Antman, Elliott M; Braunwald, Eugene; Giugliano, Robert P
Abstract: Background: The relative efficacy and safety profile of the oral Factor Xa inhibitor edoxaban compared with warfarin in patients with atrial fibrillation and established coronary artery disease (CAD) has not been analyzed. Materials and methods: In the ENGAGE AF–TIMI 48 trial, two edoxaban regimens were compared with warfarin in 21, 105 patients with atrial fibrillation and CHADS2 ⩾2. We analyzed the primary trial endpoints (efficacy: stroke or systemic embolic event, safety: International Society on Thrombosis and Haemostasis major bleeding) in patients with versus without CAD, and used interaction testing to assess for treatment effect modification. Results: The 4510 patients (21.4%) with known CAD were older, more likely male, on aspirin, with lower creatinine clearance and higher CHADS2 and HAS-BLED scores ( p <0.001 for each). Treatment with the higher-dose edoxaban regimen (versus warfarin) in patients with known CAD tended to have a greater reduction in stroke/systemic embolic event compared with patients without CAD (CAD: hazard ratio 0.65 (0.46–0.92) versus no CAD: hazard ratio 0.94 (0.79–1.12), p -INT 0.062) and also in myocardial infarction (CAD: hazard ratio 0.69 (0.49–0.98) versus no CAD: hazard ratio 1.24 (0.89–1.72), p -INT 0.017), while there was a similar reduction in bleeding irrespective of CAD status (hazard ratio 0.81 and 0.80, p -INT 0.97). Presence or absence of CAD did not modify the efficacy or safety profile of the lower-dose edoxaban regimen (versus warfarin). Conclusion: The reduction in ischemic events with the higher-dose edoxaban regimen versus warfarin was greater in patients with CAD, while bleeding was significantly reduced with edoxaban regardless of CAD status. The efficacy and safety profile of the lower-dose edoxaban regimen relative to warfarin was unaffected by CAD status.